Metformin, oral contraceptives or both to manage oligo-amenorrhea in adolescents with polycystic ovary syndrome? A clinical review. (May 2014) - Palomba, Stefano; Materazzo, Caterina; Falbo, Angela; Orio, Francesco; La Sala, Giovanni Battista; Sultan, Charles
Abstract The management of oligo-amenorrhea in adolescent patients with polycystic ovary syndrome (PCOS) represents an important and difficult challenge. Metformin and/or oral contraceptives (OCs) are different strategies widely proposed in these patients. The objective of the current review was to provide an overview on the use of metformin and/or OCs for the management of oligo-amenorrhea in adolescents with PCOS underlining their potential risks and benefits in order to help the clinician to choose the best patients' tailored treatment.